Revision of the genus Corythalia C.L. Koch, 1850, part 1: Diagnosis and new species from South America (Araneae: Salticidae: Salticinae: Euophryini) - Bayer, Steffen; Höfer, Hubert; Metzner, Heiko (Zootaxa, 2020)
We propose a revision of the spider genus Corythalia C.L. Koch, 1850 (Salticidae: Euophryini) with a revised genus diagnosis based on examination of all species available to us. In this paper we redescribe all previously described species from South America with revised species diagnoses and describe 20 new species from South America (and the nearby islands). For C. latipes, the type species of the genus Corythalia, a neotype is designated. In total, 52 nominal species of the genus are herein treated, 46 species are recognized as valid. The females of C. waleckii Taczanowski, 1871, C. luctuosa Caporiacco, 1954 and C. latipes (C.L. Koch, 1846) are described for the first time. Corythalia sellata Simon, 1901, erroneously considered as nomen nudum in the present version of the World Spider Catalog, is here recognised as a valid species. Corythalia fulgipedia Crane, 1948 is also considered a valid species and is removed from the synonymy of C. tropica (Mello-Leitão, 1939). One name is considered a nomen dubium (Corythalia variegata Caporiacco, 1954), two are nomina nuda (C. major Simon, 1901; C. dimidiata Simon, 1901). Two species are transferred to other genera: C. argyrochrysos (Mello-Leitão, 1946) to Pachomius Peckham & Peckham, 1896 as Pachomius argyrochrysos (Mello-Leitão, 1946), comb. nov. and C. heliophanina (Taczanowski, 1871) to Neonella Gertsch, 1936, as Neonella heliophanina (Taczanowski, 1871), comb. nov. under incertae sedis. One species is synonymised: C. barbipes (Mello-Leitão, 1939) is a junior synonym of C. cincta (Badcock, 1932), syn. nov. The new Corythalia species are: C. conferta sp. nov. (♂♀, Brazil), C. concinna sp. nov. (♀, Brazil), C. drepane sp. nov. (♂♀, Brazil), C. drepanopsis sp. nov. (♀, Brazil), C. antepagmenti sp. nov. (♂♀, Brazil), C. ricti Bayer, sp. nov. (♂, Guyana), C. protensa sp. nov. (♂, Brazil), C. gasnieri sp. nov. (♂, Brazil), C. verhaaghi sp. nov. (♀, Brazil), C. scutellaris Bayer, sp. nov. (♂♀, Ecuador), C. dakryodes Bayer, sp. nov. (♀, Colombia), C. foelixi Bayer, sp. nov. (♂♀, French Guiana), C. longiducta sp. nov. (♀, Brazil), C. latior sp. nov. (♂, Bolivia), C. trochophora Bayer, sp. nov. (♂, Ecuador), C. lineata Bayer, sp. nov. (♂, Guyana), C. hamulifera Bayer, sp. nov. (♂, Ecuador), C. tribulosa sp. nov. (♂, Colombia), C. flagrans sp. nov. (♂, Brazil) and C. fragilis sp. nov. (♂♀, Brazil). Illustrations are provided for all of the new species and for all (primary) type specimens of the species re-described. Hypotheses of possible relationships among the different species of Corythalia are discussed.